Real-world experiences with brentuximab vedotion-based regimens in systemic anaplastic large cell lymphoma: a multi-center retrospective study - Zhao, Zhiqiang; Yu, Qinchuan; Su, Liping; He, Jianxia; Tao, Jie; Xi, Yanfeng; Guo, Yujiao; Luo, Yanhong; Wang, Lieyang (Frontiers in Oncology, 2025)
BackgroundBrentuximab vedotin (BV) has demonstrated high remission rates in clinical trials for systemic anaplastic large cell lymphoma (sALCL), yet its real-world effectiveness in China remains unconfirmed. This retrospective observational study evaluates BV-based regimens in patients with sALCL, treated from 2020 to 2023.MethodsA multi-center observational retrospective study was conducted on patients with sALCL received BV plus cyclophosphamide, doxorubicin, and prednisone (CHP) upfront or BV plus gemcitabine, oxaliplatin(GemOx), gemcitabine, cisplatin, dexamethasone(GDP), or isocyclophosphamide, carboplatin, etoposide (ICE)for later lines. Primary endpoints were complete response rate (CRR) and overall response rate (ORR); secondary endpoints included progression-free survival (PFS), overall survival (OS), duration of response (DOR), and the incidence of adverse events (AEs).ResultsAmong the 38 patients (28 newly diagnosed and 10 with refractory/relapsed disease), the ORR were 100% (with 89.3% CR) for newly diagnosed patients and 70% (with 50% CR) for refractory/relapsed patients. The median duration of response was 14 months for newly diagnosed patients and 23.8 months for those with refractory/relapsed disease. 2-year Survival rates were 100% for newly diagnosed patients and 80% for refractory/relapsed patients, with 2-year PFS rates of 92.8% and 70%, respectively. Neurological toxicities were commonly observed but resolved following the completion of treatment.ConclusionBV has proven to be effective and well-tolerated in real-world settings for the treatment of sALCL, reinforcing its potential as a promising option for first-line or subsequent therapy. The sustained efficacy observed post-CR suggests that these patients may have a prolonged disease control.